Genetics and marker-assisted breeding for sex expression in cucumber - Dhall, R. K.; Kaur, Harleen; Manchanda, Pooja; Eshanee (Frontiers in Genetics, 2023)
Cucumber is an important vegetable crop to have an accessible draft genome, which significantly expedited the research in various fields of molecular genetics. Cucumber breeders have been employing various methodologies to improve the yield and quality of the crop. These methodologies comprise enhancement to disease resistance, use of gynoecious sex types and their association with parthenocarpy, alterations in plant architecture, as well as enhancement of genetic variability. The genetics of sex expression is a complex trait in cucumbers but is very significant for the genetic improvement of cucumber crop. In this review, an explanation the current status of gene(s) involvement and their expression studies, inheritance of genes, molecular markers, and genetic engineering associated with sex determination have been given. Besides, the role of ethylene in sex expression and sex-determining genes of ACS family have also been discussed. No doubt, gynoecy is an important trait among all sex forms of cucumber for heterosis breeding but if it is associated with parthenocarpy, then fruit yield can be enhanced to greater extent under favourable conditions. However, little information is available with regard to parthenocarpy in gynoecious type cucumber. This review sheds light on genetics and molecular mapping of sex expression and could be beneficial especially to cucumber breeders and other scientists working on crop improvement via traditional and molecular assistant approaches.